CLASSROOM EXPERIMENT AS A TEACHING METHOD IN NATURAL RESOURCE AND ENVIRONMENTAL ECONOMICS COURSE EKSPERIMEN KELAS SEBAGAI METODE PEMBELAJARAN DALAM MATA AJAR EKONOMI SUMBER DAYA ALAM DAN LINGKUNGAN - ALIN HALIMATUSSADIAH (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2014)
The use of classroom experiment as teaching method in economic courses is increasing overtime. However, it is not widely used in developing world. In the experiment, students can learn using their own experience how economic agents behave and how they make decisions in a certain situation setting. This paper aims to describe the advantage of the method, practical issues in conducting classroom experiment, and examples of two classrooms experimental games in natural resource and environmental economics course: a public goods game and a CPR (common pool resource) game. In the games we introduce different rules of the game to give an understanding the impact of different rules of the game to the result of the game. We also discussed the relation between individual characteristics and his/her decision in the game. Keywords: classroom experiment, public goods game, CPR (common-pool resource) game, natural resource and environmental economics